SOFTWARE TOOL FOR ASSESSING THE ECOLOGICAL THREAT ON THE WATERWORKS - A. A. Zinoviev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The necessity of automation calculating the parameters of an emergency in an accident on hydrological structures is examined. A mathematical model for predicting hydrological parameters emergency fracture waterworks is given. A software module for automated forecasting and assessment of the situation in an emergency situation and the possible consequences of flooding in case of a breakthrough water node is developed.